Karakteristik Ruang dalam Masjid Agung Cianjur dalam Kajian Tipologi Arsitektur - Rendi Muhammad Zaelani; Heru Wibowo; Marwoto Marwoto (Fakultas Teknik - Universitas Bung Karno, 2024)
The Great Mosque of Cianjur, established since 1810 AD, stands as a significant cultural heritage, playing a crucial role in the history and life of the Cianjur community. As a center for religious activities, the spatial characteristics within the mosque become the focus of this research. Through a qualitative descriptive research methodology and direct observation, the study identifies spatial typologies, including the porch, ablution area, prayer hall, mihrab, and pulpit, describing their unique characteristics. In the spatial hierarchy, distinctions in the level of sanctity are evident, where the ablution area/toilet serves as the initial point with a lower level of sanctity, the porch functions as a transitional and social area, the prayer hall serves as the central place of worship, while the mihrab and pulpit exhibit the highest level of sanctity. These findings provide a profound understanding of the structure and function of each space within the context of the grand mosque's architecture.The research does not only depict the physical spaces but also comprehends the significance and functions, both spiritual and practical. The results make a valuable contribution to developing an architectural perspective of the mosque as a place of worship and a center for social activities, with the hope of serving as a foundation for further developments in religious architecture. In conclusion, the Great Mosque of Cianjur exhibits diverse spatial typologies and hierarchies, reflecting historical and cultural heritage while meeting contemporary needs.